KONSEP METODE ITERASI VARIASIONAL - Yuliani '; Leli Deswita; Agusni ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
We discuss a basic concept of variational iteration method for solving partial differential equations. Variational iteration method, which can be used for ﬁnding iterative formula, consists of three basic concepts, namely a general Lagrange multiplier, a restricted variation and a correction functional.